A process synthesis approach to low-pressure methanol/dimethyl ether co-production from syngas over gold-based catalysis - Mpela, Arthur Nseka (My University, 2009)
Catalysts are involved in a very large number of processes leading to the production of industrial chemicals, fuels, pharmaceutical, and to the avoidance, as well as the clean-up of environmental pollutants. In respect to the latter aspect, efforts are being made by different stake-holders (governments, researchers, industrials, etc) in order to prevent or to minimize pollution of our cities. A notably way to reduce pollution for a friendly environment is to make use of clean fuels. After years of research work, it is only recently that dimethyl ether alone or when combined with methanol has been identified as a potential alternative clean fuel. Nonetheless, the technology used for the methanol synthesis from syngas requires high pressure (>120 atm) to reach an acceptable CO conversion. The dimethyl ether production from methanol in a separate unit makes DME more expensive than methanol. However, the transformation of syngas directly into dimethyl ether can be used to relieve the thermodynamic constraints requiring operation at high pressure. If the synthesis of methanol and dimethyl ether takes place in the same reactor, the process should, in principle, be able to operate at a much lower pressure, making it a potentially cheaper process to produce methanol and dimethyl ether. The catalysts that need to be used for this coproduction have to be catalytically stable, selective and able to catalyze the main reactions (methanol and dimethyl ether synthesis) involved in this process at the same temperature. Unfortunately, existing commercial methanol/DME catalysts are not able to function efficiently in the presence of large concentrations of water or at high temperature. Thus, it is relevant to have a catalyst satisfying the above criteria. Recently, it has been reported that a supported gold catalyst could be used for methanol synthesis; accordingly this study has developed bifunctional gold-based catalysts for the methanol and DME synthesis. This study utilized process synthesis approach to determine the optimal operating conditions for methanol/dimethyl ether production that yielded results used to drive an experimental programme to get the most useful information for designing a process route. In a comparative way and by using the feed compressor work load per unit of valuable material generated as objective function, this study showed that the system where methanol is co-produced with DME is more efficient than the one involving the production of methanol alone and this is applicable for the operating reactor temperatures of 500-700K and the loop pressure ranging from 10 to 100 atm. The catalysts systems chosen in this study were consisted in the physical mixture of gold-based catalysts incorporating respectively gamma-alumina and zeolite-Y. The gold-based catalysts were prepared by a co-precipitation method, then characterized by XRD, Raman Spectrometry and Transmission Electron Microscopy and, afterwards tested using a 1/4 inch tubular fixed bed reactor between 573 and 673K at 25 atm. Amongst the catalysts tested at 673K, and 25 atm, 5%Au/ZnO/γ-Al2O3 produced both methanol and dimethyl ether with moderate yield, whereas 5%Au/ZnO/LZ Y-52 gave high dimethyl ether selectivity (75.7%) with a production rate of 252.3 μmol.h-1.g -1 cat . The presence of hydrocarbons detected by the GC-FID in the gas products requires that further investigations be done to determine the eventual source and optimize this new catalyst system based on gold for a large scale coproduction of methanol and dimethyl ether from syngas.
Keywords: process synthesis; methanol/dimethyl ether; syngas; gold-based catalysis